The directives speech act found in the adventures of huckleberry finn novel - Puspasari, Ni Kadek Riska; Suastini , Ni Wayan; Pratiwi , Desak Putu Eka (Institut Pariwisata dan Bisnis Internasional, 2022)
This study is concerned with analyzing the research entitled The Directives Speech Act Found in The Adventures of Huckleberry Finn novel. This research is concerned with identifying the directives speech act used by the characters, how often the types of directives speech act occurred, and which types appeared most frequently in the novel. This research utilized a qualitative method, which is the data were achieved by reading the novel attentively. Five types of directives speech act were discovered in the utterance of the characters in The Adventures of Huckleberry Finn novel as a result of this analysis. Those are: warning, forbidding, asking, requesting and telling. The qualitative method was applied to find out the frequency and the types of directive speech act used in The Adventures of Huckleberry Finn novel. The researcher found five types: warning 8 data or 10%, forbidding 6 data or 9% , asking 45 data or 57%, requesting 8 data or 10%, and telling 11 data or 14% used in The Adventure of Huckleberry Finn novel. The most frequent type used was asking acts ( 45 utterances or 57% from total data).